Knowledge, attitudes, and practices of nurses on catheter-associated urinary tract infection control in a tertiary hospital in Manila - Abad, Peter James B.; Cabanding, Lea Andrea G.; Co, Grace Cecile W.; Cunanan, Justine N.; Cunanan, Kristina Bernadette L.; Ellano, Cresilda Katrina S.; Macose, Kristine Cynthia D.; Matabang, Maria Angela M.; Montilla, Precious Juzenda S.; Pizarro, Maureen Marie D.; Remolar, Arian Alexis A.; See, Francis Elmer B. (Manila College of Nursing University of the Philippines Manila, 2010)
The study aims to determine the factors that may significantly affect the knowledge, attitude and practices of nurses in pay wards from those in charity wards regarding Foley catheter care and management centered at infection prevention and control. Through review of related literature, four factors came up that were found to be associated with catheter-associated UTIs: length of experience, patient load, seminar/training experience, and availability of resources for Foley catheter care. A survey quantitative design was utilized in this study. Self-administered questionnaires were distributed to the nurses of three charity and three pay wards, where their length of experience, patient load, seminar/training experience, availability of resources for Foley catheter care, knowledge, attitudes, and self-reported practices regarding Foley catheter care and management were measured. Demographic characteristics of the sample population were described using descriptive statistics. Most of the study's respondents were female. The charity ward nurses’ mean age was 29.1 years, while the pay ward nurses’ was 37.6 years.Average length of experience of nurses from the charity ward was 4.24 years, while that of pay ward nurses was 7 years. Only less than a third of both charity and pay ward nurses have attended at least one seminar regarding indwelling catheter care. The respondents from the charity wards’ mean number of patients handled per shift (14) was lower than that of their counterparts in the pay wards (29). Most of the respondents from both ward groups claimed to have available resources for catheter care in their respective wards. Through regressional analysis of the knowledge scores as well as the four factors from the RRL, it was found out that attendance to seminars is the only factor that has a significant individual effect on the knowledge of charity ward nurses. Patient load and seminar have significant individual effects on their level self-reported practice, while length of experience, patient load, and seminars has significant individual effects on their attitude. On the other hand, none of the factors have a significant individual effect on the level of knowledge and attitude of pay ward nurses, while patient load is the only factor that has a significant individual effect in their self-reported practice. ltem analysis of the answers of the respondents was also done to give further depth to the survey done. Lastly, the nurses’ perceived factors affecting their knowledge, attitudes, and self-reported practices were also identified and grouped into themes.
Research (In partial fulfillment of the requirements of the course N121.1: Intensive Nursing Experience, Hospital-based) -- University of the Philippines Manila, March 2010.
Keywords: Intensive nursing experience -- Hospital-based.